Drug release kinetics of temperature sensitive liposomes measured at high-temporal resolution with a millifluidic device. (18th August 2018) - Burke, Caitlin; Dreher, Matthew R.; Negussie, Ayele H.; Mikhail, Andrew S.; Yarmolenko, Pavel; Patel, Aakash; Skilskyj, Brenden; Wood, Bradford J.; Haemmerich, Dieter
Abstract: Purpose: Current release assays have inadequate temporal resolution ( ∼ 10 s) to characterise temperature sensitive liposomes (TSL) designed for intravascular triggered drug release, where release within the first few seconds is relevant for drug delivery. Materials and methods: We developed a novel release assay based on a millifluidic device. A 500 µm capillary tube was heated by a temperature-controlled Peltier element. A TSL solution encapsulating a fluorescent compound was pumped through the tube, producing a fluorescence gradient along the tube due to TSL release. Release kinetics were measured by analysing fluorescence images of the tube. We measured three TSL formulations: traditional TSL (DPPC:DSPC:DSPE-PEF2000, 80:15:5), MSPC-LTSL (DPPC:MSPC:DSPE-PEG2000, 85:10:5) and MPPC-LTSL (DPPC:MMPC:PEF2000, 86:10:4). TSL were loaded with either carboxyfluorescein (CF), Calcein, tetramethylrhodamine (TMR) or doxorubicin (Dox). TSL were diluted in one of the four buffers: phosphate buffered saline (PBS), 10% bovine serum albumin (BSA) solution, foetal bovine serum (FBS) or human plasma. Release was measured between 37–45 °C. Results: The millifluidic device allowed measurement of release kinetics within the first few seconds at ∼5 ms temporal resolution. Dox had the fastest release and highest release %, followed by CF, Calcein and TMR. Of the four buffers, release was fastest in human plasma, followed by FBS, BSA and PBS. Conclusions: The millifluidic device allows measurement of TSL release at unprecedented temporal resolution, thus allowing adequate characterisation of TSL release at time scales relevant for intravascular triggered drug release. The type of buffer and encapsulated compound significantly affect release kinetics and need to be considered when designing and evaluating novel TSL-drug combinations.